Prevalence and perception of dental fluorosis among the school-going children and its impact on academic performance - Nivaditha Balamurali; Noorul Sabina Mohamed Thowbieck; Syeda Safoora Amreen; Divyadharshini Chandrasekaran; Kalaivani Karthikeyan; I Anand Sherwood (Wolters Kluwer Medknow Publications, 2020)
Aim: The prevalence of dental fluorosis in Southern India has been reported to be on higher side. In Madurai district, Tamil Nadu, the dental fluorosis incidence among 13-15-year-old school children was observed at 87.7%. The aim of the present investigation is to analyze the prevalence of dental fluorosis among 12-14-year-old school-going children and understand its impact on their academic performance. Materials and Methods: A total 693 students from four different schools were screened for dental fluorosis and severity using Thylstrup-Fejerskov index. Students' academic performance, class attendance, awareness about the condition, esthetic perception about dental fluorosis, and friends' attitude toward their teeth were evaluated. Nonparametric Mann-Whitney U and Kruskal-Wallis tests were employed to assess the influence of dental fluorosis presence on the academic performance. Results: Four hundred and thirteen (59.6%) students had dental fluorosis, and the mean number of teeth affected was 4.15 ± 1.70. Significantly (P < 0.05), marks obtained in each subject, average total marks scored in the last examination, and class attendance percentage were lower in individuals with dental fluorosis. Conclusions: School performance getting significantly affected by the presence of dental fluorosis needs to be further investigated in a controlled environment. Brown stains in dental fluorosis were considered to be of esthetic concern than white opacities among the children.